Manajemen Pelayanan Kesehatan Jamaah Haji di Puskesmas Kalisat Kabupaten Jember - Purwita Dwi Arysca Pratiwi; Eri Witcahyo; Yennike Tri Herawati (FORIKES, 2022)
The health efforts provided to the pilgrims in all the activities of organizing the pilgrimage from the first stage to the third stage are carried out in curative and rehabilitative forms. Achieving quality Hajj health services requires management that regulates the implementation of Hajj health services. The purpose of this study was to examine the management of health services for pilgrims at Kalisat Public Health Center, Jember Regency using the theory of Planning, Organizing, Staffing, Directing, Coordinating, Reporting, and Budgeting (POSDCORB). This research was a case study research with a qualitative approach. The key informants in this study were 2 people consisting of the Hajj Health Coordinator of the Jember District Health Office and the Head of the Kalisat Health Center; the main informants consisted of 2 people, namely the Kalisat Health Center Hajj Coordinator and health center officers; while the additional informants consisted of 3 pilgrims in Kalisat District. Data were collected through in-depth interviews and document studies. Based on the results of the study, it was known that most of the informants understand the process of planning and management of hajj health services carried out at the health center, and there are still a few problems regarding the misunderstanding of hajj pilgrims.Keywords: Hajj health service management; planning; organizingABSTRAK Upaya kesehatan yang diberikan kepada jamaah haji pada seluruh kegiatan penyelenggaraan ibadah haji mulai dari tahap pertama hingga tahap ketiga dilakukan dalam bentuk kuratif dan rehabilitatif. Tercapainya pelayanan kesehatan haji yang berkualitas memerlukan manajemen yang mengatur pelaksanaan pelayanan kesehatan haji. Tujuan penelitian ini adalah mengkaji pengelolaan pelayanan kesehatan jamaah haji di Puskesmas Kalisat, Kabupaten Jember menggunakan teori Planning, Organizing, Staffing, Directing, Coordinating, Reporting, dan Budgeting (POSDCORB). Penelitian ini merupakan penelitian studi kasus dengan pendekatan kualitatif. Informan kunci dalam penelitian ini adalah 2 orang yang terdiri atas koordinator kesehatan haji Dinas Kesehatan Kabupaten Jember dan Kepala Puskesmas Kalisat; informan utama terdiri dari 2 orang yaitu Koordinator Kesehatan Haji Puskesmas Kalisat dan petugas puskesmas; sedangkan informan tambahan terdiri dari 3 jamaah haji di Kecamatan Kalisat. Data dikumpulkan melalui wawancara mendalam dan studi dokumen. Berdasarkan hasil penelitian, diketahui bahwa sebagian besar informan memahami proses perencanaan dan manajemen pelayanan kesehatan haji yang dilakukan di puskesmas, dan masih terdapat sedikit masalah tentang ketidakpahaman jamaah haji.Kata kunci: manajemen pelayanan kesehatan haji; perencanaan; pengorganisasian